Ground Penetrating Radar for Buried Explosive Devices Detection: A Case Studies Review. Issue 4 (4th July 2022) - Machado Brito-da-Costa, Andreia; Martins, Diana; Rodrigues, Diogo; Fernandes, Luís; Moura, Rui; Madureira-Carvalho, Áurea
ABSTRACT: Geophysical techniques can be successfully applied towards the detection of buried explosive devices, the ground-penetrating radar (GPR) being an example of one such method. This technology works through emission and reception of electromagnetic radio waves being thus able to detect the presence of a subsurface object fundamentally due to reflections from contrasting electromagnetic properties between the object and the surrounding medium (e.g., soil). Many factors can influence the success of a GPR survey (e.g., target type, soil type, environmental conditions, GPR antenna frequency, data processing techniques), being essential to know and understand their likely effects before performing GPR studies, mainly in real cases. In this paper, through the analysis of case studies related to the use of GPR technology towards the detection of buried explosive devices, we intend to arrange and layout the main prior knowledge that a forensic geophysical expert must have when dealing with this type of fieldwork.